Ethics and Aesthetics in Advanced Editing: Balancing Creative Vision with Ethical considerations - Uwem A. AKPAN; Uduot IWOK, PhD; Ifeanyi M. NWOKEOCHA, PhD; Gospel AMAEFULE (International Journal of Business and Quality Research, 2024)
The study examined ethics and aesthetics in advanced editing: balancing creative visions with ethical considerations. The study adopted four objectives which were to examine the interplay between creative visions and ethical considerations in the editing process; explore the ethical principles and guidelines that inform editing decisions in relation to aesthetic choices; analyze how editors navigate conflicts between aesthetic preferences and ethical responsibilities; identify best practices for integrating ethical considerations into aesthetic choices to maintain the integrity of the content. The study adopted two the social responsibility and ethical theories. The study concluded that In order to achieve this balance, editors must be well-versed in ethical principles and guidelines that inform their work. They should consider the impact of their aesthetic choices on the audience, stakeholders, and individuals involved, and seek feedback and collaboration to ensure multiple perspectives are taken into account. Transparency is key to building trust with the audience, as editors should be open about their editing process and disclose any conflicts of interest. The study recommended that Media professionals should Familiarize themslves with industry standards, codes of conduct, and legal considerations to ensure that editing decisions align with ethical boundaries. By establishing a strong ethical framework, media editors can navigate conflicts between creative visions and ethical responsibilities more effectively.